Shedding the Burden, Moving Forward: A Comparative Study of Select Contemporary Indian and American Breast Cancer Narratives - Bhattacharyya, Mahua (IIT(BHU) Varanasi, 2024)
Abstract is available in the attachment.
Keywords: Humanistic Studies